The assessment of usefulness of innovative instrumental treatments for non‑invasive reduction of a double chin (Journal of Face Aesthetics, 2020)
One of the most common defects in the facial area is the so‑called “double chin”. The problem affects both males and females, and its occurrence is associated with several different factors. It is commonly believed that this defect is a result of excessive adipose tissue location in the lower face. However, the problem seems to be more complex. It is also facilitated by the loss of firmness and elasticity of ageing skin, and in many persons the existence of a double chin results from their anatomical structure, and therefore is determined by genes. Besides, incorrect posture accentuates the defect. It may seem that such minor change does not affect the appearance to a large extent. Whereas, in most cases it causes that the border between the jaw line and the neck disappears what, in turn, distorts the face contour. All this makes a person with a double chin look much older than he or she in fact is. This leads to negative self‑esteem, makes people feel ashamed, and quite often is the main reason for avoiding interaction with other people. So, it is no wonder that persons with such defect seek methods offering its mitigation.Surgical methods give quick and satisfactory effects. However, they are fraught with high risk of complications, and as such they cause anxiety and ultimately discourage patients from making the decision. Luckily, significant improvements in the field of cosmetology and aesthetic surgery offer a wide range of possibilities to reduce a double chin in a manner which is completely non‑invasive, pain free, and does not require long lasting convalescence. In this case, very good results are achieved with the use of innovative technological solutions, such as HIFU and cryolipolysis. Aim. The main aim of this paper is to assess the efficiacy of cryolipolysis in the double chin reduction and the description of innovative instrumental methods allowing for a non‑invasive reduction of this defect.
Keywords: double chin; face contour; HIFU; cryolipolysis; adipose tissue reduction; non‑invasive facelift